Nobody Likes Ike: The National Civic Art Society and Commemorative Containment in Washington, D.C. Issue 1 (1st January 2023) - Keohane, Jennifer
ABSTRACT: This essay explores the history of the Eisenhower Memorial in Washington, D.C. as a lens on the shifting nature of U.S. public memory. The National Civic Art Society (NCAS) opposed the memorial plans in a vitriolic report. I argue that the NCAS seeks to regain control of D.C.'s memorial landscape via commemorative containment. Their rhetoric on the memorial emphasizes scarcity, suggesting only certain commemoration is appropriate. In narrating Eisenhower's biography, attacking the process, and defining citizenship as obedience, the NCAS report commemoratively contains the memorial. Doing so centers whiteness and limits the multiplicity of stories told on the National Mall.